Global analysis of a multi-group viral infection model with age structure. Issue 16 (10th December 2021) - Yang, Yu; Zou, Lan; Takeuchi, Yasuhiro
ABSTRACT: In this paper, we consider a multi-group viral infection model with age structure and general incidence. We first give the positivity and boundedness of the solutions. Then, we study the local stability of the equilibria and uniform persistence of this model. Moreover, we establish the global results by constructing Lyapunov functionals. Finally, two special cases are presented to verify the validity of our theoretical results.